2018
DOI: 10.1002/jum.14870
|View full text |Cite
|
Sign up to set email alerts
|

TIRADS Interobserver Variability Among Indeterminate Thyroid Nodules: A Single‐Institution Study

Abstract: Objectives-A high proportion of cytologically indeterminate, Afirma Gene Expression Classifier "suspicious" thyroid nodules are benign. The Thyroid Imaging Reporting and Data System (TIRADS), was proposed by the American College of Radiology in 2017 to help classify thyroid nodules based on ultrasound characteristics in a standardized fashion to guide management. We aim to determine the interobserver variability of TIRADS classification among cytologically indeterminate and Afirma suspicious nodules.Methods-We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
2
14
2
Order By: Relevance
“…Interobserver variability among radiologists and sonographers is an important consideration to improve TI-RADS performance. In a retrospective analysis of 127 nodules using ACR TI-RADS, Sahli et al (2019) showed that while TI-RADS interobserver variability was fair (0.6 to 0.74), shape and margin criteria were the biggest sources of disagreement (poor; 0.359 and 0.192, respectively) [25]. Interestingly, in a separate study exploring sonographer performance and interobserver variability, Wildman-Tobriner et al (2020) showed that sonographers also struggle with margins.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver variability among radiologists and sonographers is an important consideration to improve TI-RADS performance. In a retrospective analysis of 127 nodules using ACR TI-RADS, Sahli et al (2019) showed that while TI-RADS interobserver variability was fair (0.6 to 0.74), shape and margin criteria were the biggest sources of disagreement (poor; 0.359 and 0.192, respectively) [25]. Interestingly, in a separate study exploring sonographer performance and interobserver variability, Wildman-Tobriner et al (2020) showed that sonographers also struggle with margins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, observer variabilities of TIRADS regarding the interpretation of ultrasound features or FNA recommendation are receiving increasing attention [67][68][69]. Experienced and less experienced radiologists may have different interpretations of thyroid nodule ultrasound features and therefore requires a continuous and specialized training for residents to improve the agreement and performance thyroid ultrasound in residents [70,71].…”
Section: Ultrasound Lexicon Of Thyroid Nodulesmentioning
confidence: 99%
“…A number of studies have been published on the interobserver agreement in the assessment of individual thyroid ultrasound imaging features, which ranges from poor to almost perfect, depending on the feature and study (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . Liu et al (34) conducted a meta-analysis of seven studies assessing inter-observer agreement published up to December 2018, including a total of 927 patients (18)(19)(20)(21)(22)(23) .…”
Section: Inter-and Intra-observer Agreement In the Assessment Of Indi...mentioning
confidence: 99%
“…A number of studies have been published on the interobserver agreement in the assessment of individual thyroid ultrasound imaging features, which ranges from poor to almost perfect, depending on the feature and study (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) . Liu et al (34) conducted a meta-analysis of seven studies assessing inter-observer agreement published up to December 2018, including a total of 927 patients (18)(19)(20)(21)(22)(23) . They calculated the pooled agreement between examiners in the assessment of individual features in thyroid ultrasound images, with the following results: substantial agreement for structure (0.61; 95% Cl: 0.55-0.66) and presence of calcifications (0.71; 95% Cl: 0.65-0.77), moderate agreement for echogenicity (0.58; 95% Cl: 0.51-0.64), shape (0.53; 95% Cl: 0.45-0.62), and the presence of echogenic foci, including punctate echogenic foci/microcalcifications, macrocalcifications, peripheral calcifications, and comet tail artefacts (0.43; 95% Cl: 0.32-0.54), and fair agreement for margins (0.40; 95% Cl: 0.32-0.48).…”
Section: Inter-and Intra-observer Agreement In the Assessment Of Indi...mentioning
confidence: 99%